1999
DOI: 10.1038/sj.jim.2900751
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomonas herbicidovorans MH: a versatile phenoxyalkanoic acid herbicide degrader

Abstract: Sphingomonas herbicidovorans MH was isolated from a dichlorprop-degrading soil column. It is able to grow on phenoxyalkanoic acid herbicides, such as mecoprop, dichlorprop, 2,4-D, MCPA, and 2,4-DB. Strain MH utilizes both enantiomers of the chiral herbicides mecoprop and dichlorprop as sole carbon and energy sources. Enantiomer-specific uptake systems are responsible for transporting the acidic substrates across the cell membrane. Catabolism is initiated by two enantiomer-specific alpha-ketoglutarate-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 25 publications
2
36
0
1
Order By: Relevance
“…Previously, a S. herbicidovarans MH has been described that degrades phenoxyalkanoic acid herbicides such as mecorprop, dichlorprop, 2,4-D, 4-chloro-2-methylphenoxyacetic acid (MCPA), and 2,4-dichlorophenoxybutanoic acid (2,4-DB) 20,24) , although this strain could not degrade 2,4,5-T 20) . In this study, group S(III) strains, most homologous with S. herbicidovarans, were isolated as 2,4,5-T-degraders.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a S. herbicidovarans MH has been described that degrades phenoxyalkanoic acid herbicides such as mecorprop, dichlorprop, 2,4-D, 4-chloro-2-methylphenoxyacetic acid (MCPA), and 2,4-dichlorophenoxybutanoic acid (2,4-DB) 20,24) , although this strain could not degrade 2,4,5-T 20) . In this study, group S(III) strains, most homologous with S. herbicidovarans, were isolated as 2,4,5-T-degraders.…”
Section: Discussionmentioning
confidence: 99%
“…7), and preliminary data from H.-P. E. Kohler (EAWAG, Dübendorf, Switzerland) (personal communication) indicate that C. testosteroni KF-1 utilizes 3-C4-SPC enantiomer specifically. It seems likely that many SPCs are utilized enantiomer specifically, but the mechanisms involved (two enantiomer-specific transport systems and two enantiomer-specific oxygenases, as described by Kohler [19]) remain to be explored. The degradative pathway(s) for SPCs was the subject of much speculation (3) until Schulz et al (32) showed the involvement of inducible 4-sulfocatechol 1,2-dioxygenase in the degradation of 2-C4-SPC and Dong et al (5) found high activity of the enzyme in a mixed culture which degraded SP(d)Cs.…”
Section: Discussionmentioning
confidence: 99%
“…However, both enantiomers were and still are applied as racemic mixtures, resulting in the introduction of large amounts of unwanted chemicals into the environment (10,50,51). Sphingomonas herbicidovorans MH, an Alphaproteobacterium, is able to grow on both enantiomers of mecoprop and dichlorprop, as well as on 2,4-D, as sole carbon and energy sources (21,24,54). In batch cultures, this organism degrades the two enantiomers of mecoprop and dichlorprop sequentially, and the (S) enantiomers are degraded first (25,32).…”
mentioning
confidence: 99%